(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
This research aimed to determine and analyze the relation of stress and emotional eating to diet quality and nutrient intake among final-year nutrition students at IPB University. The design of this research was a cross-sectional study with 50 final-year Community Nutrition IPB students as subjects. The research was conducted online from May to June 2023. Stress level were measured using Depression, Anxiety, Stress Scale 42 (DASS-42) questionnaire and emotional eating was assessed using the Adult Eating Behavior Questionnaire (AEBQ). Most of the subjects experienced mild stress (34%) and emotional undereating (EUE) (60%). Most of the subjects fell to the “HEI need improvement” category (70%). The analysis results showed that stress had no relationship with emotional overeating (EOE) and emotional undereating (EUE) (p>0.05), EOE and EUE had no relationship with diet quality (p>0.05). Stress levels had a negative correlation with diet quality (p=0.000;r=-0.479). Stress levels had positive correlation with the adequacy of energy (p=0.015;r=0.344), protein (p=0.004;r=0.396), and fat (p=0.005;r=0.388). EOE had positive correlation with the intake of energy (p=0.020;r=0.329), protein (p=0.049;r=0.280), fat (p=0.028;r=0.312), and carbohydrate (p=0.019;r=0.330). It was also found that EUE had negative correlation with protein intake (p=0.043;r=-0.288) and carbohydrate intake (p=0.028;r=-0.311).